Environmental and crustacean zooplankton variations in a reservoir during four hydrological years - George, Catherine (2010)
Azibo is a meso-eutrophic reservoir located in the Portuguese part of R. Douro catchment (Latitude: 41 D34'32, 25"N; longitude: 6- 53'51, 63"W; altitude: 624m). As it is utilized mainly for recreation and for some urban water supply the water level variations are not very accentuated. This fact allows the evaluation of the effects of environmental variations and of other disturbance phenomena on the reservoir limnology without the interference of water level fluctuations.